First-principles study of a molecular adsorption of fluorine on monolayer MoS2 - Paudyal, Hari; Pantha, Nurapati; Adhikari, Narayan Prasad (BIBECHANA, 2015)
We have performed density functional theory (DFT) based first-principles calculations to study the stability, geometrical structures and electronic properties of pure monolayer Molybdenum disulphide (MoS2) and Fluorine (F2) adsorbed monolayer MoS2 within the DFT-D2 level of approximations. Present study shows that a F2 molecule adsorbed MoS2 monolayer system is stable. From the geometry and in- formation of adsorption energy of F2 molecule on the different occupation sites of MoS2 monolayer, it has been found that Fluorine prefers atomic adsorption above sulphur (S) atom. The binding energy per equivalent molecular Fluorine above the sulfur (S) atom is found to be 1.83 eV. The electronic structure calculations of MoS2 and F2 adsorbed MoS2 monolayer shows that there is a band gap of 1.14 eV and 1.01 eV respectively, at the Fermi level. Further, the symmetry of total DOS for up and down spin calculations reveals that the F2 adsorbed MoS2 monolayer is non-magnetic as similar to that of pure MoS2 monolayer. The projected density of states (PDOS) of a F2 adsorbed MoS2 monolayer is studied to understand the weighted contributions of different orbitals. BIBECHANA 13 (2016) 50-59